2017
DOI: 10.1016/j.cattod.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress towards the electrosynthesis of ammonia from sustainable resources

Abstract: Ammonia (NH 3 ) is a key commodity chemical of vital importance for fertilizers. It is made on an industrial scale via the Haber Bosch process, which requires significant infrastructure to be in place such that ammonia is generally made in large, centralized facilities. If ammonia could be produced under less demanding conditions, then there would be the potential for smaller devices to be used to generate ammonia in a decentralized manner for local consumption. Electrochemistry has been proposed as an enablin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
467
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 625 publications
(505 citation statements)
references
References 62 publications
6
467
0
Order By: Relevance
“…[23][24][25] A variety of factors need to be analyzed when selecting the cell material such as system operating temperature, current density, pressure, and conductivity which affect the ammonia production rate. It is important to note that conductivity of a solid electrolyte increases exponentially with temperature and by reducing cell thickness as reported by Giddey et al 26 Kyriakou et al 27 recently reported extensive literature data about low temperature, medium temperature and high temperature electrochemical NH 3 28 presented the recent developments in electrochemical NH 3 production and they categorized the sources of proton as water, hydrogen and sacrificial proton donors. They resulted that the techniques keeping the temperatures in the range of 100…”
mentioning
confidence: 94%
“…[23][24][25] A variety of factors need to be analyzed when selecting the cell material such as system operating temperature, current density, pressure, and conductivity which affect the ammonia production rate. It is important to note that conductivity of a solid electrolyte increases exponentially with temperature and by reducing cell thickness as reported by Giddey et al 26 Kyriakou et al 27 recently reported extensive literature data about low temperature, medium temperature and high temperature electrochemical NH 3 28 presented the recent developments in electrochemical NH 3 production and they categorized the sources of proton as water, hydrogen and sacrificial proton donors. They resulted that the techniques keeping the temperatures in the range of 100…”
mentioning
confidence: 94%
“…under ambient conditions.D ensity functional theory calculations reveal that the active orbital and electrons of zigzag and diff-zigzag type edges of FL-BP NSs enable selective electrocatalysis of N 2 to NH 3 via an alternating hydrogenation pathway.T his work proves the feasibility of using an onmetallic simple substance as an itrogen-fixing catalyst and thus opening an ew avenue towardst he development of more efficient metal-free catalysts. [12][13][14][15] To this end, the search for an electrocatalytic NRR center in recent years has mainly focused on transition-metal-based materials. [1] At present, the energyintensive Haber-Bosch process is the main artificial synthesis route for ammonia, and this process uses more than 1% of global annual energy consumption and produces carbon dioxide emissions.…”
mentioning
confidence: 99%
“…[12][13][14][15] To this end, the search for an electrocatalytic NRR center in recent years has mainly focused on transition-metal-based materials. [12][13][14][15] To this end, the search for an electrocatalytic NRR center in recent years has mainly focused on transition-metal-based materials.…”
mentioning
confidence: 99%
“…[7,8] High temperature and pressure however is involved in the Haber-Bosch process for industrial-scale NH 3 production. [12,13] Although tackling the energy-and H 2 -intensive operations by the Haber-Bosch process, it is still challenged with N 2 activation and electrocatalysts for N 2 reduction reaction (NRR) are a prerequisite. In this context, a less energydemanding and environmentally benign alternative process for NH 3 production is highly desirable.…”
mentioning
confidence: 99%
“…[12,13] Although tackling the energy-and H 2 -intensive operations by the Haber-Bosch process, it is still challenged with N 2 activation and electrocatalysts for N 2 reduction reaction (NRR) are a prerequisite. [12,13] Although tackling the energy-and H 2 -intensive operations by the Haber-Bosch process, it is still challenged with N 2 activation and electrocatalysts for N 2 reduction reaction (NRR) are a prerequisite.…”
mentioning
confidence: 99%